What drives citations in tourism research? - Huang, Songshan (Sam); Shao, Yuhong; Zhang, Di (Annals of tourism research, 2025)
•A comprehensive analysis of what factors drive citations in tourism research.•Analyze 27 SSCI and 30 ESCI tourism and hospitality journals.•Article-related factors include age, number of keywords, and special issue articles.•Author esteem and review articles are positively related to citations.•Being published in an ABDC A* or SSCI Q1 journal significantly predicts citations.